Circadian light therapy and light dose for depressed young people: a systematic review and meta-analysis - Chen, Ranpeng; Yan, Yonghong; Cheng, Xiang (Frontiers in Public Health, 2024)
Background Empirical evidence has shown that light therapy (LT) can reduce depression symptoms by stimulating circadian rhythms. However, there is skepticism and inconclusive results, along with confusion regarding dosing. The purpose of this study is to quantify light as a stimulus for the circadian system and create a dose-response relationship that can help reduce maladies among adolescents and young adults (AYAs). This will provide a reference for light exposure and neural response, which are crucial in the neuropsychological mechanism of light intervention. The study also aims to provide guidance for clinical application. Methods The latest quantitative model of CLA (circadian light) and CSt,f (circadian stimulus) was adopted to quantify light dose for circadian phototransduction in youth depression-related light therapy. Articles published up to 2023 through Web of Science, Cochrane Library, Medline (OVID), CINAHL, APA PsycINFO, Embase, and Scholars were retrieved. A meta-analysis of 31 articles (1,031 subjects) was performed using Stata17.0, CMA3.0 (comprehensive meta-analysis version 3.0) software, and Python 3.9 platform for light therapy efficacy comparison and dose-response quantification. Results Under various circadian stimulus conditions (0.1 < CSt,f < 0.7) of light therapy (LT), malady reductions among AYAs were observed (pooled SMD = −1.59, 95%CI = −1.86 to −1.32; z = −11.654, p = 0.000; I2 = 92.8%), with temporal pattern (p = 0.044) and co-medication (p = 0.000) suggested as main heterogeneity sources. For the efficacy advantage of LT with a higher circadian stimulus that is assumed to be influenced by visualization, co-medication, disease severity, and time pattern, sets of meta-analysis among random-controlled trials (RCTs) found evidence for significant efficacy of circadian-active bright light therapy (BLT) over circadian-inactive dim red light (SMD = −0.65, 95% CI = −0.96 to −0.34; z = −4.101, p = 0.000; I2 = 84.9%) or circadian-active dimmer white light (SMD = −0.37, 95% CI = −0.68 to −0.06; z = −2.318, p = 0.02; I2 = 33.8%), whereas green-blue, circadian-active BLT showed no significant superiority over circadian-inactive red/amber light controls (SMD = −0.21, 95% CI = −0.45 to 0.04; z = −2.318, p = 0.099; I2 = 0%). Overall, circadian-active BLT showed a greater likelihood of clinical response than dim light controls, with increased superiority observed with co-medication. For pre-to-post-treatment amelioration and corresponding dose-response relationship, cumulative duration was found more influential than other categorical (co-medication, severity, study design) or continuous (CSt,f) variables. Dose-response fitting indicated that the therapeutic effect would reach saturation among co-medicated patients at 32–42 days (900–1,000 min) and 58–59 days (1,100–1,500 min) among non-medicated AYAs. When exerting high circadian stimulus of light therapy (0.6 < CSt,f < 0.7), there was a significantly greater effect size in 1,000–1,500 min of accumulative duration than <1,000 or >1,500 min of duration, indicating a threshold for practical guidance. Limitations The results have been based on limited samples and influenced by a small sample effect. The placebo effect could not be ignored. Conclusions Although the superiority of LT with higher circadian stimulus over dimmer light controls remains unproven, greater response potentials of circadian-active BLT have been noticed among AYAs, taking co-medication, disease severity, time pattern, and visual characteristics into consideration. The dose-response relationship with quantified circadian stimulus and temporal pattern had been elaborated under various conditions to support clinical depression treatment and LT device application in the post-pandemic era.